Managing registration of new student intake using online registration new student intake system (ORNSIS) integrated barcode technology - Muhammad Syafiq, Johari (2011)
The rapid progress in education impacts the significant requirement to manage the educational globalization resources through the use of modem technology.In addition, an online system is the electronic interactive medium that delivers information to users via telephone lines to personal computers (PCs) or via cables to terminals,This paper presents on bow to manage the registration of new student intake by using Online Registration New Student Intake System (ORNSIS).Integrated barcode technology with ORNSIS has been developed in order to overcome the manual system weakness,which involves the registration through the traditional methods and time consuming.Understanding the importance and limitations the register process,ORNSIS is a collaborative of web application concept that provides a platform for University Malaysia Pahang administrator to monitor the progress of each new student who did the register online.It has been developed by using the PHP language,Dreamweaver cs4 and database MySQL in the Windows 7.By using ORNSIS,the actual number of student will register in university can be obtain,thus decrease the time-consuming in registration event.